Teaching Technostress and Perception of the Quality of Service in a Private University in Lima - Alcas Zapata, Noel (2019)
The objective of this study is to know the association between teaching techno-stress and the perception of the quality of service within a Peruvian university. The psychophysiological disturbances that technological means could be causing when coming into contact with workers are analyzed as part of the impact of new technologies in work spaces. In this sense, a quantitative and non-experimental investigation was carried out in which data were collected through the application of two instruments: the Red Questionnaire (2004) which contains 16 items linked to techno-stress and the ServQual Model with 22 items which measured the perception of the quality of service. Both instruments passed the reliability test through the Cronbach's alpha coefficient, obtaining a value of, 891 and, 911, respectively. Through probabilistic sampling, 154 teachers were considered as samples. For the descriptive and inferential statistical analysis, contingency tables were generated, using the Pearson Chi-Square test statistic, from which it is concluded that there is an association between the teaching Techno-stress and the perception of the quality of service (X2 (6 ) = 85,731 and the Asymptotic Sig (bilateral) or p_value = 0.000 <0.05). Likewise, it is concluded that there is an association between the Teaching Techno-stress and the perceptions of each of the theoretical dimensions of service quality: tangible elements (X2 (6) = 112,055 and the Asymptotic Sig (bilateral) or p_value = 0.000 <0.05), reliability (X2 (6) = 63,859 and the Asymptotic Sig (bilateral) or p_value = 0.000 <0.05), responsiveness (X2 (6) = 35,580 and the Asymptotic Sig (bilateral) or p_value = 0.000 <0.05), security (X2 (6) = 42.838 and the Asymptotic Sig (bilateral) or p_value = 0.000 <0.05) and empathy (X2 (6) = 23.633, with six degrees of freedom (6 ) and the Asymptotic Sig (bilateral) or p_value = 0.000 <0.05).